ANALISIS PROSEDUR PENGOBATAN MENGGUNAKAN BPJS KESEHATAN - Tamrin Lanori; Selfiani Selfiani; Yudhistira Adwimurti; Hendi Prihanto; Usmar Usmar (Unversitas Prof. Dr. Moestopo (Beragama), 2022)
This research was conducted with the aim of empirically examining the effect of claims, premiums and bureaucracy on procedural accountability at the puskesmas in South Tangerang. The sample criteria that meet as many as 25 puskesmas, the type of research carried out is using primary data with the research object being BPJS users. The data collection was carried out by distributing research questionnaires directly to respondents by visiting the Puskesmas in South Tangerang City. The research method used in this study is the causal method. The researcher used multiple linear regression analysis using SPSS 22 tools. The results showed that claims and bureaucracy had no effect on procedural, while premiums had an effect on procedural accountability.